Songorine modulates macrophage polarization and metabolic reprogramming to alleviate inflammation in osteoarthritis - He, Xi-Xi; Huang, Yuan-Jun; Hu, Chun-Long; Xu, Qiong-Qian; Wei, Qing-Jun (Frontiers in Immunology, 2024)
Introduction Osteoarthritis (OA) is a prevalent joint disorder characterized by multifaceted pathogenesis, with macrophage dysregulation playing a critical role in perpetuating inflammation and joint degeneration. Methods This study focuses on Songorine, derived from Aconitum soongaricum Stapf, aiming to unravel its therapeutic mechanisms in OA. Comprehensive analyses, including PCR, Western blot, and immunofluorescence, were employed to evaluate Songorine's impact on the joint microenvironment and macrophage polarization. RNA-seq analysis was conducted to unravel its anti-inflammatory mechanisms in macrophages. Metabolic alterations were explored through extracellular acidification rate monitoring, molecular docking simulations, and PCR assays. Oxygen consumption rate measurements were used to assess mitochondrial oxidative phosphorylation, and Songorine's influence on macrophage oxidative stress was evaluated through gene expression and ROS assays. Results Songorine effectively shifted macrophage polarization from a pro-inflammatory M1 phenotype to an anti-inflammatory M2 phenotype. Notably, Songorine induced metabolic reprogramming, inhibiting glycolysis and promoting mitochondrial oxidative phosphorylation. This metabolic shift correlated with a reduction in macrophage oxidative stress, highlighting Songorine's potential as an oxidative stress inhibitor. Discussion In an in vivo rat model of OA, Songorine exhibited protective effects against cartilage damage and synovial inflammation, emphasizing its therapeutic potential. This comprehensive study elucidates Songorine's multifaceted impact on macrophage modulation, metabolic reprogramming, and the inflammatory microenvironment, providing a theoretical foundation for its therapeutic potential in OA.